Walter Kaufmann: Philosopher, Humanist, Heretic by Stanley Corngold - Jude P. Dougherty (Studia Gilsoniana, 2019)
This paper is a review of the book: Stanley Corngold, Walter Kaufmann: Philosopher, Humanist, Heretic (Princeton: Princeton University Press, 2018). The author concludes that Corngold’s book acquaints the reader not only with the thought of Walter Kaufmann, but also with the thought of a prominent, late twentieth century generation that in effect rejected the source of the very culture that nourished it.